The seal of biliteracy : case studies and considerations for policy implementation - Heineke, Amy J.; Davin, Kristin (Contemporary language education (Greenwich, Conn.), 2020)
"This edited volume examines the Seal of Biliteracy (SoBL), a relatively new policy initiative that has received little attention in scholarly and practical literature. The contributions seek to expand the literature by presenting case studies of policy implementation in diverse contexts across the United States. This book is organized into four sections: (1) introduction to the SoBL, including history of the policy initiative and national trends in policy design and implementation, (2) case studies of macro-level policy implementation, including a diverse array of contexts across the country that have approached the SoBL in unique ways (e.g., legislation v. educational code, prioritizing world v. home languages), (3) case studies of micro-level implementation, including schools and districts that award the SoBL to diverse student populations through various language programs (e.g., English-dominant v. linguistically diverse; world language v. dual-language programs), and (4) conclusions and future directions, including actionable next steps for policy makers, administrators, educators, and researchers. Many national professional organizations would have interest in this text, including National Association for Bilingual Education (NABE), Teachers of English to Speakers of Other Languages (TESOL), the American Council for Teaching of Foreign Languages (ACTFL), and the National Council of State Supervisors for Languages (NCSSFL), as well as local affiliates for bilingual, English as a second language (ESL), and world language education (e.g., California Association of Bilingual Education; Illinois Council for Teaching Foreign Languages)"--